ANALISIS PENINGKATAN SECURITY CULTURE TERHADAP KEAMANAN PENERBANGAN DI BANDAR UDARA INTERNASIONAL SULTAN HASANUDDIN MAKASSAR - OCTAVIANIE, ADHITYA; SANJAYA; WIWIK, BERNADETTA; NUR, MULYADI (Jurnal Penjaminan Mutu, 2023)
Sultan Hasanuddin Airport is one of the airports managed commercially by PT. Angkasa Pura I. In the future, this airport will continue to be developed to the ultimate stage. This study aims to analyze the relationship between aspects of security culture and efforts to maintain and improve aviation security at Sultan Hasanuddin International Airport Makassar. Data collection in this research was carried out by observing, interviewing, and questionnaire. There are 8 (eight) aspects that need to be considered to see the implementation of a security culture at an airport. The research conducted at Sultan Hasanuddin Makassar Airport looks at the application of a safety culture through these 8 (eight) aspects. Based on the 8 (eight) aspects that have been assessed, the results are generally very good. This result is certainly a positive thing because the result is a reflection of the implementation of a security culture or security culture at the Sultan Hasanuddin Makassar International airport.